Real-world deployment of lateral flow SARS-CoV-2 antigen detection in the emergency department to provide rapid, accurate and safe diagnosis of COVID-19. Issue 4 (December 2021) - Merrick, B.; Noronha, M.; Batra, R.; Douthwaite, S.; Nebbia, G.; Snell, L.B.; Pickering, S.; Galao, R.P.; Whitfield, J.; Jahangeer, A.; Gunawardena, R.; Godfrey, T.; et al.
Summary: Background: Point-of-care (POC) SARS-CoV-2 lateral-flow antigen detection (LFD) testing in the emergency department (ED) could inform rapid infection control decisions but requirements for safe deployment have not been fully defined Methods: Review of LFD test results, laboratory and POC-RT-PCR results and ED-performance metrics during a two-week high SARS-CoV-2 prevalence period followed by several months of falling prevalence. Aim: Determine whether LFD testing can be safely deployed in ED to provide an effective universal SARS-CoV-2 testing capability. Findings: 93% (345/371) of COVID-19 patients left ED with a virological diagnosis during the 2-week universal LFD evaluation period compared to 77% with targeted POC-RT-PCR deployment alone, on background of approximately one-third having an NHS Track and Trace RT-PCR test-result at presentation. LFD sensitivity and specificity was 70.7% and 99.1% respectively providing a PPV of 97.7% and NPV of 86.4% with disease prevalence of 34.7%. ED discharge-delays (breaches) attributable to COVID-19 fell to 33/3532 (0.94%) compared with the preceding POC-RT-PCR period (107/4114 (2.6%); p=<0.0001). Importantly, LFD testing identified 1 or 2 clinically-unsuspected COVID-19 patients/day. Three clinically-confirmed LFD false positive patients were appropriately triaged based on LFD action-card flowchart, and only 5 of 95 false-negative LFD results were inappropriately admitted to non-COVID-19 areas where no onward-transmission was identified. LFD testing was restricted to asymptomatic patients when disease prevalence fell below 5% and detected 1–3 cases/week. Conclusion: Universal SARS-CoV-2 LFD testing can be safely and effectively deployed in ED alongside POC-RT-PCR testing during periods of high and low disease prevalence.